What Impact does Internet of Things have on Project Management in Project based Firms? - Vadlamudi, Siddhartha (Asian Business Review, 2016)
The highest benefit of IT spans through the enabling of personnel to attain their organizational goals. However, acquiring the IT skills that were not aware of in the past will boost and enhance the personnel for greater performance. IoT technology gives understanding from novel data generated and gives solutions. Therefore, allowing organizations to access new strategies via technological innovation will bring about efficiency and productivity with the project lifecycle. However, this project aimed at assessing the impact of IoT on PM in project-based organizations. A qualitative method of investigation was adopted through interviews and discussions with 9 selected respondents. The result shows the benefit and the usefulness of IoT in project-based organizations. This was assessed using the five project management model namely initiating, planning, executing, control and monitoring, and closing. It is established that the impact of IoT can be seen using any of the five stages. Hence, this study identifies the most critical elements of any project-based organization to include people, possessing on personnel and how their impact the invention of project-based organizations.